Perancangan Alat Ukur Kadar Gula Pada Produk Pangan Menggunakan Sensor Kapasitor Keping Sejajar Berbasis Mikrokontroler ATMega8535 - Hardaniyus Sanjaya; Amir Supriyanto; Gurum Ahmad Pauzi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
It has been realizeda instrument measuring of sugar content using sensor chip capasitors parallel based on microcontroller ATMega8535. The research objective design and realize a detector sugar in food product. The design of study was conducted by placing the sensor chip capasitors parallel as input voltage, then the signal will be condition by the Wheatstone Bridge which will be forwarded to the microcontrollel ATMega8535 and displayed on the LCD. The result of measurements performed on the percentage of food product with sugar content of the flour by 4,77%, tapioca starch 33,33%, flour maizeaku 40,69%, tepung ketan putih 32,74%, tepung beras putih 36,96%, sagu 49,46% and beras merah 20,32%. The data were analyzed and obtained the standard deviation by the change of voltage